Update on Prevention of Cardiovascular Disease in Adults With Type 2 Diabetes Mellitus in Light of Recent Evidence. Issue 8 (25th August 2015) - Fox, Caroline S.; Golden, Sherita Hill; Anderson, Cheryl; Bray, George A.; Burke, Lora E.; de Boer, Ian H.; Deedwania, Prakash; Eckel, Robert H.; Ershow, Abby G.; Fradkin, Judith; Inzucchi, Silvio E.; Kosiborod, Mikhail; et al.
<x xml:space="preserve">Abstract</x> Cardiovascular disease risk factor control as primary prevention in patients with type 2 diabetes mellitus has changed substantially in the past few years. The purpose of this scientific statement is to review the current literature and key clinical trials pertaining to blood pressure and blood glucose control, cholesterol management, aspirin therapy, and lifestyle modification. We present a synthesis of the recent literature, new guidelines, and clinical targets, including screening for kidney and subclinical cardiovascular disease for the contemporary management of patients with type 2 diabetes mellitus.